PENGUATAN MODEL PERENCANAAN STRATEGIS UNTUK PEMBERDAYAAN EKONOMI KOMUNITAS LOKAL - Yohan Purnawan; Melisa Nur Asima Sidabutar; Julina Purba (Nusantara Hasana Journal, 2024)
This community service program (PkM) aims to develop and test an applicable strategic planning model to strengthen the economic empowerment of local communities. Common problems faced by partners include economic programs that are ad hoc in nature, not yet based on data regarding potentials and challenges, weak value chain mapping, limited access to markets and capital, and the absence of measurable performance indicators. The method was carried out through participatory assessment, mapping of potentials and stakeholders, SWOT/TOWS and value chain analysis, formulation of vision–mission–objectives, development of program portfolios (quick wins–medium term), determination of KPIs and financing plans, as well as assistance in pilot implementation. The main outputs include a Strategic Plan for Economic Empowerment (roadmap), a set of planning tools (templates) and SOPs, and a monitoring dashboard to ensure sustainability.